Thermal and chemical variations in metamorphic rocks in Nautanen, Gällivare, Sweden - Tollefsen, Elin (Stockholms universitet, Institutionen för geologiska vetenskaper, 2014)
This study focuses on the geology of the Nautanen area. It is part of the SGU-financed project, Metamorphic Map of Sweden, which aims to compile metamorphic data from Sweden and takes the form of a number of Bachelor and Master projects. The main metamorphic event in the Nautanen area is the Svecokarelian Orogeny (1.96 – 1.75 Ga). The samples are metamorphosed sedimentary and volcanic rocks, which were intruded by intermediate to mafic intrusions and a later granite intrusion. The supracrustal rocks are folded and the Nautanen Deformation Zone (NDZ) traverses the area in a NW to SE direction. Petrographic studies, XRF analysis and THERMOCALC were used to estimate pressure and temperature and to elucidate evidence of fluid mobility. The average pressure was assumed to be below 4 kbar because of the presence of andalusite. The lowest and highest temperatures for metamorphism were 474±43°C and 681±14°C, with highest temperatures recorded nearest to the granite intrusion. XRF analysis revealed high concentrations of Ba (up to 7000 ppm) in the NDZ. High concentrations of Ba, skarn formation and replacement of garnet by chlorite indicate fluid-controlled metamorphism in the NDZ. The increasing temperature towards the granite intrusion suggests regional or contact prograde metamorphism that need not be related to the NDZ. Metamorphic Map of Sweden, SGU-project